A molecular signature of dormancy in CD34+CD38- acute myeloid leukaemia cells - Al-Asadi, Mazin Gh.; Brindle, Grace; Castellanos, Marcos; May, Sean; Mills, Ken I.; Russell, Nigel; Seedhouse, Claire; Pallis, Monica (Impact Journals, 2017)
Dormant leukaemia initiating cells in the bone marrow niche are a crucial therapeutic target for total eradication of acute myeloid leukaemia. To study this cellular subset we created and validated an in vitro model employing the cell line TF-1a, treated with Transforming Growth Factor β1 (TGFβ1) and a mammalian target of rapamycin inhibitor. The treated cells showed decreases in total RNA, Ki-67 and CD71, increased aldehyde dehydrogenase activity, forkhead box 03A (FOX03A) nuclear translocation and growth inhibition, with no evidence of apoptosis or differentiation. Using human genome gene expression profiling we identified a signature enriched for genes involved in adhesion, stemness/inhibition of differentiation and tumour suppression as well as canonical cell cycle regulation. The most upregulated gene was the osteopontin-coding gene SPP1. Dormant cells also demonstrated significantly upregulated beta 3 integrin (ITGB3) and CD44, as well as increased adhesion to their ligands vitronectin and hyaluronic acid as well as to bone marrow stromal cells. Immunocytochemistry of bone marrow biopsies of AML patients confirmed the positive expression of osteopontin in blasts near the para-trabecular bone marrow, whereas osteopontin was rarely detected in mononuclear cell isolates. Unsupervised hierarchical clustering of the dormancy gene signature in primary acute myeloid leukaemia samples from the Cancer Genome Atlas identified a cluster enriched for dormancy genes associated with poor overall survival.